Silenciamentos e/ou apagamentos de temas insurgentes nos currículos dos anos iniciais do ensino fundamental: percepções e desafios de uma atuação docente crítica-decolonial - (:unkn) unknown (Universidade Estadual de Goiás, 2024)
In this research, my general objective is to question the (non)existence of curricular content related to insurgent themes in public schools in Guapó for the early years of elementary education and its connection to teachers' educational practices. My specific objectives are to: a) discuss the presence and/or erasure of insurgent themes in the formal curriculum; and b) reflect on the manifestation and/or silencing of these themes in educational practices. This research draws on the following sources for building empirical material: normative documents (BNCC and Expanded DCGO); transcripts of conversations held with teachers working in this school system; and a questionnaire administered via Google Forms. The epistemological frameworks intersecting with this study are grounded in decolonial perspectives (Mignolo, 2008, 2010, 2020, 2021; Quijano, 2000, 2005, 2010; Maldonado-Torres, 2007; Walsh, 2007, 2013, among others); curriculum studies (Silva, 2007; Lopes and Macedo, 2011; Candau, 2010, 2020; Süssekind, 2019, among others); and intercultural education and decolonial pedagogy (Walsh, 2009, 2013, 2018; Mota Neto, 2016; Ortiz-Ocaña, Arias López, and Pedrozo Conedo 2018b; Fuly, 2022, among others). The paths taken in this study to produce knowledge seek to disobey traditional paradigms, using a perspective that recognizes and confronts the hierarchies of knowledge and power present in the academic and social context. Given the understanding that the world is permeated by latent colonialities that continue to reproduce their power structures, and aiming to transcend them, I seek to align this research with the decolonial perspective, which adopts a stance of political/ethical/epistemic resistance, aiming to open avenues for rethinking research approaches. In this regard, I employ decolonial efforts (Silvestre, 2017) to discuss school curriculum (formal curriculum and educational practices). Thus, the study reveals that curricula reflect power struggles, where decisions about content, methods, and values are influenced by different ideological, cultural, and political perspectives; that curricula in Brazil have historically been influenced by colonialities; that from the 1980s, curricula aligned with neoliberal policies, as reflected in the BNCC, which standardizes market-focused guidelines and marginalizes themes that enable critical educational practices; that the Expanded DCGO, while including advances in diversity, still carries colonial practices and neoliberal influences, contributing alongside the BNCC to maintain an instrumental education oriented toward the market; and that our educational practices result from a constant negotiation between the formal curriculum and the school reality. Therefore, this research contributes to understanding the urgency of strengthening a decolonial and intercultural pedagogy that promotes emancipation and fosters the formation of critical citizens aware of diversity, dismantling the logic of exclusion brought about by colonialities and neoliberal educational policies. It also highlights the challenge of increasing teacher engagement and education for critical, insurgent, and decolonial practices.
Silencing and/or Erasing Insurgent Themes in Curricula of the Early Years of Elementary Education: Perceptions and Challenges of a Critical-Decolonial Teaching Approach
Keywords: Currículo escolar; Pedagogia decolonial - Interculturalidade crítica; Currículo - Temas insurgentes; Curriculum; Decolonial pedagogy - Critical interculturality; Curriculum - Insurgent themes; CIENCIAS HUMANAS::EDUCACAO